An analysis of Alvin Goldman’s naturalized epistemology - Elias Ifeanyi E Uzoigwe (International Journal of Humanities and Innovation (IJHI), 2020)
This work, “An Analysis of Alvin Goldman’s Naturalistic Epistemology,” aims to present Alvin Goldman's contributions in an epistemic bent. As a philosophy, epistemology has significantly advanced right from the classic, medieval, modern, and contemporary epochs. The effects of postmodernist thinkers’ radical approach to philosophy are evident in almost all philosophy branches. With the notion of doing epistemology through science championed by W.V.O. Quine, Alvin Goldman, John Kuhn, and some other scholars have raised objections and counter objections to such a deconstructionist mindset within the epistemic circle. Expectedly, these naturalistic epistemologists had discontinuity with one another in their positions. Goldman is concerned with such traditional epistemological problems as developing an adequate theoretical understanding of knowledge and justified belief. This paper shows that in his naturalistic discontinuity with Quine, Alvin Goldman did not conceive epistemology as part of science the same way Quine conceived it. Goldman’s view that answering traditional epistemological questions requires both a priori philosophy and the application of scientific results. Goldman’s naturalism is the view that epistemology “needs help” from science. His primary concern is in traditional epistemological problems, including developing an adequate theoretical understanding of knowledge and justified belief. In this paper, I see Goldman’s divergence in the opinion of his naturalistic epistemology with Quine and other naturalistic epistemologists not as a problem but as indeed part of epistemic consolidation. In the course of this work, analytic, evaluation, library research, and descriptive methods, and internet materials, were employed.